A Molecular Relay‐Modified CdS‐Sensitized Photoelectrochemical Cell for Overall Water Splitting. Issue 9 (5th August 2016) - Shen, Chao; Chua, Chin Sheng; Lim, Yee‐Fun; Liu, Jie; Wang, Xingzhu; Liu, Bin; Wang, Qing
Abstract: A novel approach to enhance the photocurrent and photostability of semiconductor‐sensitized photoelectrochemical cells (PECs) with a nonsacrificial electrolyte by grafting the CdS surface with a molecular relay, 4‐( N, N ‐diphenylamino)benzoic acid (DPABA) is reported. Using this modification, the PECs are able to perform overall water splitting instead of only hydrogen generation. The probable reasons for the improvement are that the photogenerated holes in the CdS valence band could be rapidly removed by DPABA, which facilitates charge separation and thus suppresses the photocorrosion process. The use of such a method might further improve the performance of overall water splitting, together with superior light‐absorption sensitizers and more suitable molecular relays with better oxygen evolution reaction catalytic properties. Abstract : Graft and evolve : A novel approach to achieving overall water splitting in semiconductor‐sensitized photoelectrochemical cells with a nonsacrificial electrolyte by grafting the CdS surface with a molecular relay, 4‐( N, N ‐diphenylamino)benzoic acid (DPABA), is reported.